Pemanfaatan Aplikasi Pembelajaran Oleh Siswa Selama Kegiatan Belajar Daring Di SMA 3 Kuala Kapuas - Wahidin (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
The development of information technology has driven changes in the learning system, including at the secondary school level. The use of learning applications has become a primary alternative to support the online learning process, particularly to accommodate the needs for access to materials, communication, and evaluation. This study focused on the use of learning applications by students at Kuala Kapuas 3 High School during online learning activities. The purpose of this study was to determine the types of applications used, the frequency and duration of their use, how students utilize them, the obstacles encountered, and the strategies they use to overcome these obstacles. This study used a qualitative approach with descriptive methods. The subjects were 11th and 12th grade students, while the objects were students' activities in using learning applications. Data collection techniques were conducted through interviews, observation, and documentation, followed by analysis through data reduction, data presentation, and drawing conclusions. The results showed that students actively use various applications such as Google Classroom, WhatsApp, and Zoom. Application use provides benefits in terms of learning flexibility, increased independence, and effective communication. Obstacles encountered included network disruptions, limited devices, and learning boredom. Students developed various strategies such as sharing devices, finding locations with stable signal, and forming online study groups.